Attitude, reporting behavour and management practice of occupational needle stick and sharps injuries among hospital healthcare workers in Bale zone, Southeast Ethiopia: a cross-sectional study. Issue 1 (December 2015) - Bekele, Tolesa; Gebremariam, Alem; Kaso, Muhammedawel; Ahmed, Kemal
Abstract Background Although the prevalence of blood borne pathogens in many developing countries is high, documentation of infections due to occupational exposure is limited. Seventy percent of the world's HIV infected population lives in Sub-Saharan Africa, but only 4 % of cases are reported from this region. Under reporting of needle stick and/or sharps injuries in healthcare facilities was common. Methods An institutional based cross-sectional study was conducted in December 2014 among healthcare workers in four hospitals of Bale zone, Southeast Ethiopia. A total of 362 healthcare workers were selected randomly from each of the working departments. Data were collected using self-administered questionnaire and were entered using Epi-Info version 3.5 and analysed using SPSS version 20.0. Multivariable logistic regression analysis was used to identify independent effect of each variable on the reporting behaviour of needle stick and/or sharp injury. Results Nearly six out of ten injuries (58.7 %) were not reported to the concerned body. The main reasons for not reporting the injuries were time constraint (35.1 %), sharps which caused injury were not used on any patient (27.0 %), the source patients did not have disease of concern (20.3 %), and lack of knowledge that it should be reported (14.9 %). Half of healthcare workers (HCWs) those who experienced injury had sought medical care next to self based action. Respondents with monthly salary of 450 to 1000 Ethiopian Birr (1 US Dollar = 22.00 Ethiopian Birr) were about six times more likely to report occupational needle stick and/or sharps injury (NSSI) than HCWs with salary of 2001 to 8379 birr (AOR = 5.73). However, HCWs who had no knowledge about probability of infection transmission through NSSI and not taking any self based measures after occurrence of injury were 45 % (AOR = 0.55) and 93 % (AOR = 0.07) less likely to report occupational injury than their counterparts, respectively. Conclusions Occupational needle stick and/or sharps injuries are common among HCWs at the study area. Even though majority of respondents were concerned about the risk of NSSI exposure, most respondents did not report it to the concerned body. Therefore, provision of on job training on the risk of occupational NSSI exposure may strengthen HCWs to practice timely reporting and its management in case of occupational injury exposure.